Anti-eczema potential of three tea extracts: mechanisms of anti-inflammatory, antibacterial, antioxidant, and immunomodulatory effects - Huang, Zeting; Zhang, Lanyue; Xuan, Jie; Xu, Duoling; Weng, Jiyu; Yu, Bing; Peng, Weihua (Frontiers in Pharmacology, 2025)
BackgroundTea, with a long history in China, is known for its anti-inflammatory and antioxidant properties. Limited research exists on its use in eczema treatment. This study explores the effects and mechanisms of three tea extracts—Camellia sinensis var. assamica (Royle ex Hook.) (Theaceae) (CS), Camellia ptilophylla Hung T. Chang (Theaceae) (CP), Camellia arborescens Hung T. Chang, F. L. Yu & P. S. Wang (Theaceae) (CA). On eczema induced by 1-chloro-2,4-dinitrobenzene (DNCB) in mice and to explore the underlying anti-inflammatory and immune regulatory mechanisms.MethodsThe metabolites of tea extracts were analyzed using ultra-high performance liquid chromatography/quadrupole Orbitrap mass spectrometry (UHPLC-Q-Orbitrap-MS). A DNCB-induced dermatitis model in mice was established, with histological staining and immunohistochemistry to assess eczema lesions and cytokine expression. In vitro tests were performed on RAW 264.7 cells and HaCaT cells to analyze the effects on inflammation, immune regulation, and cell migration.ResultsAll three tea extracts alleviated DNCB-induced epidermal thickening, reduced mast cell infiltration, and decreased TNF-α and IL-1β levels. The extracts suppressed nitric oxide (NO), reactive oxygen species (ROS), and NF-κB expression. Additionally, they downregulated immune-related factors such as IL-1, IL-6, IFN-γ, and TGF-β. Scanning electron microscopy revealed morphological changes in Escherichia coli and Staphylococcus aureus.ConclusionCS, CP, and CA show potential for treating eczema, demonstrating anti-inflammatory and immune-regulatory effects. These tea extracts could serve as promising natural treatments for eczema and related inflammatory skin conditions.